Presence in Mediterranean hotspots and floral symmetry affect speciation and extinction rates in Proteaceae. Issue 2 (23rd December 2014) - Reyes, Elisabeth; Morlon, Hélène; Sauquet, Hervé
Summary: The Proteaceae is a large angiosperm family displaying the common pattern of uneven distribution of species among genera. Previous studies have shown that this disparity is a result of variation in diversification rates across lineages, but the reasons for this variation are still unclear. Here, we tested the impact of floral symmetry and occurrence in Mediterranean climate regions on speciation and extinction rates in the Proteaceae. A rate shift analysis was conducted on dated genus‐level phylogenetic trees of the Proteaceae. Character‐dependent analyses were used to test for differences in diversification rates between actinomorphic and zygomorphic lineages and between lineages located within or outside Mediterranean climate regions. The rate shift analysis identified 5–10 major diversification rate shifts in the Proteaceae tree. The character‐dependent analyses showed that speciation rates, extinction rates and net diversification rates of the Proteaceae were significantly higher for lineages occurring in Mediterranean hotspots. Higher speciation and extinction rates were also detected for zygomorphic species, but net diversification rates appeared to be similar in actinomorphic and zygomorphic Proteaceae. Presence in Mediterranean hotspots favors Proteaceae diversification. In contrast with observations at the scale of angiosperms, floral symmetry is not a trait that strongly influences their evolutionary success.